First Steps of the Mexico Twin Registry (RGMex-MexTR) at the University of Guadalajara. (16th December 2019) - Cervantes-Cardona, Guillermo A.; Cervantes-Nápoles, Tania E.; Cervantes-Guevara, Gabino; Manzo-Palomera, Olga R.; González-Ojeda, Alejandro; Silva-González, Gabriela; Fuentes-Orozco, Clotilde; Sánchez-Michel, Ángel; Nápoles-Echauri, Adriana
Abstract: Despite the well-known relevance of twin studies in the medical and social sciences and the growing number of twin registries throughout the world, Latin America has not fully incorporated into the twin research community. We describe the first steps taken toward developing a twin registry in Mexico: its aim, organization, recruiting potential and main short-term objectives.